(untitled) (Journal of Engineering, 2022)
This research aimed to develop a simulation traffic model for an urban street with heterogeneous traffic capable of analyzing different types of vehicles of static and dynamic characteristics based on trajectory analysis that demonstrated psychophysical driver behavior. The base developed model for urban traffic was performed based on the collected field data for the major urban street in Baghdad city. The parameter; CC1 minimum headway (represented the speed-dependent of the safety distance from stop line that the driver desired) justified in the range from (2.86sec) to (2.17 sec) indicated a good match to reflect the actual traffic behavior for urban traffic streets. A good indication of the convergence between simulated and field data of maximum error of 8% and below 10% for traffic flow rate and that provided a successfully simulated model by VISSIM for urban traffic behavior. The traffic speed decreased slowly, but still, variation in a large range from (30 km/hr to 55 km/hr) until a flow rate of 1000 vehicles/hr was reached, then the traffic speed decreased sharply. The dispersion between data points was caused by driver behavior and the special characteristics of the urban street. This dispersion of data points reduced and became less significant when it reached the capacity of the road. The obtained capacity value for divided urban traffic streets was (1610 vehicles/hr) with an optimum traffic density of 64 vehicles/km. Traffic simulation utilizing VISSIM parameters had been developed successfully since the simulation could estimate the field capacity with an acceptable range of error of 7.5 % (less than 10%).